Perancangan Komunikasi Visual Gerakan Sosial di Sungai Ciliwung Jakarta dengan Pendekatan Ambient Media - Rujiyanto Rujiyanto (Humaniora, 2014)
Social movement in Ciliwung river area is an informal group activity specifically focuses on environmental issues about Ciliwung river, Jakarta, by implementing or rejecting and campaigning the movement. Visual communication design of social movement is very important because good visual communication design will acquire proper visual communication and specific message to support the success of social movement. Exploration of visual communication for environmental social movement campaign to the point of finding the right communication media will train the sense of environmental problems, enrich knowledge and insight, strengthen the theory and expert opinion, as well as a reference in visual communication design. Appropriate message of visual communication will make it easier to apply the message on the media. The number of visual communications media requires careful thought to decide the use of media in social movement. Ambient mascot creation and election of new media as the media are important in the selection of environmental social movement media. Ethnography was used as method in the study and design then through library research. Field work for approximately one and a half years in the Ciliwung river environmental activist and community Betawi culture become a fundamental tool for understanding the issues arise in the environment. Research is based on participant observation that strengthens the results which can be applied in the design of visual communication. Mascot is an important finding in this design. Figure which can be a spokesperson or spokespersons for social movement in the Ciliwung river is the central figure applied in any visual message in the visual communication design. Mascot also strengthens ambient media as new media in social movement of visual communication. This visual communication design contributes to Visual Communication Design in its patterns of thinking design phase from starting stages of concept, idea, and reference data exploration, ethnography to visualization stage.